Cottage Level Cassava Starch Processing Systems in Colombia and Vietnam - Da, Guillaume; Dufour, Dominique; Giraldo Toro, Andrés; Moreno, Martín A.; Tran, Thierry; Velez, Gustavo; Sánchez, Teresa; Le-Thanh, Mai; Marouzé, Claude; Maréchal, Pierre-André (Springer, 2012)
In the tropics, cassava starch is produced at artisanal and industrial scales. This paper focuses on a new methodology enabling the technoeconomical comparison of small-scale cassava starch manufacturing process (1–5 t of starch/day) in two markedly different contexts (Colombia and Vietnam). Measurements were conducted during trial runs for each unit operation (washing/pealing, rasping, extraction and separation). Starch mass balance was calculated from sample composition (moisture, starch and crude fiber and ash content). Production capacity, water consumption, electric requirements and capital–labor costs were also measured. The manufacturing processes differed mainly on starch recovery from starch present in washed roots (65 vs. 76%), extraction capacity (0.3 vs. 0.9 t of washed roots/h), water consumption (45 vs. 21 m3/t of dry starch), energy consumption (59 vs. 55 kWh/t of starch) and production costs (1,156 vs. 162 US$/t of starch) for Colombia and Vietnam, respectively. Moreover, the effectiveness of the starch extraction process could largely be attributed to the differences in the extent of root disintegration achieved with different rasping equipment.